Design of Highly Reversible Zinc Anodes for Aqueous Batteries Using Preferentially Oriented Electrolytic Zinc. Issue 11 (10th July 2020) - Faegh, Ehsan; Ng, Benjamin; Hayman, Dillon; Mustain, William E.
Abstract: Rechargeable zinc‐based batteries have attracted a growing interest due to their intrinsic safety, low environmental impact and potentially very low cost. However, there still remains significant hurdles to achieve cells of commercial interest. Conventional commercial Zn anodes are formed from large, polycrystalline particles with limited control over the shape and size. In this study, preferentially oriented electrolytic Zn (e‐Zn) particles with hexagonal shape and controlled size (∼100 μm) were synthesized and physically characterized by SEM, XRD and BET techniques. The corrosion, discharge and cycling behavior of e‐Zn particles were analyzed in KOH alkaline media. It was found that preferentially oriented e‐Zn particles with low surface area have lower corrosion than Zn powder and 99 % reduced corrosion rate with respect to polycrystalline Zn wire. Furthermore, e‐Zn electrodes were successfully scaled up and showed remarkable reversibility in symmetric cells at a high rate of 20 mA cm −2 for 640 h. e‐Zn/KOH/MnO2 full cells were also demonstrated with ca. 6 times longer cycle life than Zn powder with a lower H2 gassing rate at 10 % Zn DoD and C/20 rate. In addition, a comparison between alkaline vs. mild acidic electrolyte was made in terms of reversibility and structural changes of preferentially oriented e‐Zn electrodes where superior cycling was observed in ZnSO4 for 2000 h. Abstract : Preferentially oriented Zn anodes : A novel Zn electrode design with high stability and reversibility in both alkaline and mild acidic media is presented. They are prepared electrolytically, allowing for controlled size, shape, and preferred crystallographic orientation, which allows Zn corrosion to be reduced and more reversible charge/discharge to be achieved.